A double blind randomized controlled trial to assess efficacy of nutritional therapy for prevention of recurrence of hepatic encephalopathy in patients with cirrhosis. Issue 3 (23rd January 2023) - Ahuja, Hardik; Sharma, Barjesh Chander; Sachdeva, Sanjeev; Mahajan, Bhawna; Sharma, Ashok; Bara, Sushma; Srivastava, Siddharth; Kumar, Ajay; Dalal, Ashok; Sonika, Ujjwal
Abstract: Background and Aim: Overt hepatic encephalopathy (OHE) has high risk of recurrence and is associated with poor survival. The role of nutrition therapy is well documented in cirrhosis, but its efficacy in preventing the recurrence of OHE has not been studied. Methods: In double blind RCT, we randomly assigned 150 patients with liver cirrhosis, with history of OHE in recent past to receive nutrition therapy (group I) or no nutrition therapy (group II) and followed up for 6 months. The primary efficacy end points were occurrence of breakthrough episodes and time to breakthrough episode of OHE. Secondary end points were OHE related hospitalizations and time to hospitalization involving OHE. Other parameters included anthropometry, changes in serum cytokines (IL‐1, IL‐6, IL‐10, and TNF‐α), endotoxin and myostatin. Results: There was significant reduction in occurrence of breakthrough episodes of OHE in group I [10 vs 36, hazard ratio 0.20; P  < 0.001], OHE‐related hospitalization [8 vs 24, hazard ratio 0.27; P  < 0.001)]. Times to breakthrough episode of OHE and OHE‐related hospitalization were longer in group I. At the end of 6 months, inflammatory and anthropometry parameters showed significant improvement in group I compared with worsening of serum albumin, anthropometric parameters, IL‐6, IL‐10 and TNF‐α in group II. At the end of 6 months, ascites (50 vs 66, P  = 0.01), gastrointestinal bleed (2 vs 11, P  = 0.007), and jaundice (16 vs 41, P  < 0.001) were lower in group I. Conclusions: Treatment with nutrition therapy prevented recurrence of OHE and decreased OHE‐related hospitalizations as compared with no nutrition therapy.